Use of Social Media among the Elderly - syamsuddin, syamsuddin (Department of Sociology Faculty of Social and Political Sciences, 2023)
There are needs of using social media for elderly, remembering of its function is very helpful to develop social relation, including to access needed important information. This conceptual article aims to know the using of social media for elderly, including the advantages and the barriers felt by the elderly within using of social media. Data and information was gathered and analyzed from any sources such as articles and any relevant sources. The result of study shows that the number of the elderly using of social media in Indonesia was increase. The variety of social media used by the elderly is almost same with the youth such Whatsapp, Facebook, Youtube, Instagram, and Twitter. The advantages felt by the elderly from social media are improving social connectivity and relation, decreasing of depression level and increasing of happiness and social role. The barriers felt by the elderly are interpersonal, functional and structural barriers. Therefore, to improve the social role of elderly mediated by social media is suggested to run a program to teach and train elderly how to use the social media effectively. Also, we need more agronomic features of social media to reduce barriers. And the most important thing is special discount from government to cover the budget internet access cost for elderly.